A Study of the influencing Factors of IPO’s Initial Abnormal Returns in ChiNext: Evidence from 319 listed companies - Dou, Dongdong (2016)
The paper investigates the underpricing phenomenon of initial public offering (IPO) in ChiNext by studying 319 IPOs from 2010 to 2012. The average underpricing for ChiNext during the sample period is about 27.8%. The study reviews the nine western theories that explain the IPO underpricing. Among them, we find winner’s curse theory, signaling theory, speculative bubble theory and information cascade theory could explain the underpricing behavior in ChiNext. The rest of the hypotheses have no explanatory power for ChiNext IPO underpricing in our study. Therefore, information asymmetry, irrational investors and speculation activity are three main reasons giving rise to IPO underpricing in ChiNext. The study selects 14 independent variables to examine the hypotheses by employing Ordinary Least Square (OLS) method.